Marine Biota and Biodiversity: A Sustainable Tourism Perspective - Dharmawan, Ni Ketut Supasti; Sarjana, Made (Advances in Tropical Biodiversity and Environmental Sciences, 2017)
Protection and conservation of marine biodiversity and their utilization based on sustainable environment, balance, and fairness play an important role in the context of sustainable tourism. The importance of protecting the availability of a healthy environment, which not only focuses on the present, but also a sustainable environment for future generations, is regulated under several provisions such as: Law of the Republic of  Indonesia Number 27 Year 2007 on the Management of Coastal Areas and Small  Islands, Law No. 32 of 2009 on the Environmental Protection and Management, Law No. 10 Year 2009 on Tourism, Law No. 5 Year 1990 on the Conservation of Biological Diversity and Ecosystems,  the UN WTO Global Code of Ethics for Tourism, and the Convention on Biological Diversity. In order to protect and conserve marine biodiversity, it is considered relevant to use deep ecology approach in realizing the presence of marine biota and sustainable biodiversity for the entire ecosystem of life, including human life ecosystems in the development of tourism activities. States and all stakeholders have responsibility for the protection and conservation of biodiversity, including sustainable development of marine biota and its diversity for tourism activities. K eywords : Biodiversity, Protection, Conservation, Responsibility, Sustainable Tourism